The Influence of Media Literacy in the Message of Diversity of Earth Convervation on the Knowledge of Indonesian Society - Kikin Yuliaty Subarsa Putri; Adamu Abbas Adamu; Saparuddin Mukhtar (Nusantara Science and Technology Proceedings)
New media gives color to human life. The messages in the new media are very helpful and some even have a negative impact on humans. The main objective of this research is to analyze the effect of the use of new media literacy in the message of diversity in the conservation of the earth to the knowledge of new media users. Concept of research is media literacy and human knowledge. Media literacy is a human ability to use new media in terms of insight, processing messages, analysis messages and evaluating messages. Message. The research method used is quantitative with respondents consisting of large cities Serang, Depok, Makassar, Bandung, Medan, and Jakarta. Reflective descriptive research is positive in both indicator variables. The influence of these two variables is positive and has a strong influence on user knowledge. Research suggestions are that all messages in new media should directly use sentences and images that are understood by users.